Upregulation of sialyltransferases ST3Gal1 and ST6Gal1 promotes stabilization of erythrocyte mass and recovery of anemia in Trypanosoma brucei brucei-infected pigs. (July 2022) - Atata, J.A.; Enam, S.J.; Ogbuagu, N.E.; Balogun, E.O.; Adamu, S.; Esievo, K.A.N.
Abstract: The role of Sialyltransferases (STs) specifically subfamilies ST3Gal1 and ST6Gal1 tissue expression was investigated in the liver and kidney of Trypanosoma brucei brucei -infected and uninfected control pigs. The study was aimed to provide emerging target for treatment. Pigs were experimentally infected with 2 × 10 6   T. b. brucei (Federe strain); parasitemia was monitored by microscopy and tissue expression levels of ST3Gall and ST6Gall in the liver and kidney were assessed using quantitative real-time polymerase chain reaction (qRT-PCR). Parasitemia were undulating and anemia occurred significantly ( P  < 0.01) on day 13 in the infected pigs with an attempt to recover toward the termination of the study on day 21. The gene expressions for hepatic and renal ST3Gal1 and ST6Gal1 were significantly ( P  < 0.0001) upregulated 5–42 folds in the infected pig compared to the non-infected control group. It was concluded from the findings in this study that increased tissue expression of ST3Gal1 and ST6Gal1 in T b. brucei- infected pigs may play a pivotal role in the resialylation of desialylated red blood cells, thereby promoting recovery of the red blood cells and stabilization of erythrocyte mass in trypanosome-infected pigs. It is recommended that the expression of serum ST3Gal1 and ST6Gal1 be investigated further, in trypano-susceptible against trypano-tolerant breeds of animals to determine the role of these genes in trypano-tolerance. Highlights: Sialyltransferase is an endogenous anemia-controlling enzyme in T. brucei brucei trypanosomiasis. Upregulation of sialyltransferase genes in T. brucei brucei -infected pigs stabilizes anemia. Hepatic and renal sialyltransferases were preferentially upregulated in T. brucei brucei trypanosomiasis.